A Novel Lecture Browser Using Key Phrases and Stream Graphs - Riedhammer, Korbinian Thomas; Nöth, Elmar; Gropp, Martin (Proc. ASRU 2011, 2011)

A Novel Lecture Browsing System using Ranked Key Phrases and StreamGraphs - Gropp, Martin; Nöth, Elmar; Riedhammer, Korbinian Thomas (Proceedings of TSD2011, 2011)

Automatic Dating of Historical Documents - Christlein, Vincent; Gropp, Martin; Maier, Andreas (Kodikologie und Paläographie im digitalen Zeitalter, 2017)
UnivIS-Import:2017-12-18:Pub.2017.tech.IMMD.IMMD5.automa_32

Technical Tools for the Analysis of High Medieval Papal Charters - Christlein, Vincent; Gropp, Martin; Maier, Andreas (Papstgeschichte im Digitalen Zeitalter. Neue Zugangsweisen zu einer Kulturgeschichte Europas, 2018)
UnivIS-Import:2018-02-22:Pub.2018.tech.IMMD.IMMD5.techni_0

THE FAU VIDEO LECTURE BROWSER SYSTEM - Riedhammer, Korbinian Thomas; Gropp, Martin; Nöth, Elmar (2012)
A growing number of universities and other educational institutions provide recordings of lectures and seminars as an additional resource to the students. In contrast to educational films that are scripted, directed and often shot by film professionals, these plain recordings are typically not post-processed in an editorial sense. Thus, the videos often contain longer periods of inactivity or silence, unnecessary repetitions, or corrections of prior mistakes. This paper describes the FAU Video Lecture Browser system, a web-based platform for the interactive assessment of video lectures, that helps to close the gap between a plain recording and a useful e-learning resource by displaying automatically extracted and ranked key phrases on an augmented time line based on stream graphs. In a pilot study, users of the interface were able to complete a topic localization task about 29% faster than users provided with the video only while achieving about the same accuracy. The user interactions can be logged on the server to collect data to evaluate the quality of the phrases and rankings, and to train systems that produce customized phrase rankings.
Keywords: automatic speech recognition; key phrase extraction; key phrase ranking; visualization; user interaction

Unsupervised Feature Learning for Writer Identification and Writer Retrieval - Christlein, Vincent; Gropp, Martin; Fiel, Stefan; Maier, Andreas (2017 14th IAPR International Conference on Document Analysis and Recognition (ICDAR), 2017)
UnivIS-Import:2018-02-22:Pub.2017.tech.IMMD.IMMD5.unsupe_6

Validierter SKT als Multimodale Telemedizinische Applikation - Soutschek, Stefan; Spiegl, Werner; Gropp, Martin; Steidl, Stefan; Nöth, Elmar; Erzigkeit, Hellmut; Hornegger, Joachim; Kornhuber, Johannes (Tagungsband zum 2. deutschen AAL-Kongress (2. Deutscher AAL (Ambient Assisted Living)-Kongress Berlin), 2009)
Ziel dieser Arbeit ist die Verringerung von Beurteilereinflüssen bei psychometrischen Tests, wie dem Syndrom-Kurztest (SKT), d.h. die Steigerung intersubjektiver Übereinstimmung der Beurteiler, durch die Erfassung validitätssteigernder Variablen mit Hilfe multimodaler Sensoren. Beispiele für solche Sensoren sind Mikrofone, Eyetracker oder Touch-Screens. Die Messung kognitiver Leistungsdefizite nimmt insbesondere bei der Diagnose und Therapiekontrolle altersassoziierter Erkrankungen – zu denen etwa die Demenzen zu zählen sind – einen wichtigen Stellenwert ein. Im Rahmen eines von der Bayerischen Forschungsstiftung (BFS) geförderten Forschungsprojektes (FitForAge) wird untersucht, ob es gelingt, ein interaktives Testsystem zur Erfassung von kognitiven Leistungsstörungen zu konstruieren, das für den Einsatz im telemedizinischen Bereich geeignet ist und vom Patienten weitestgehend selbständig ausgeführt werden kann. Als Grundlage für diese Messungen soll der SKT dienen. Der SKT ist ein international validierter Test zur Erfassung von Gedächtnis- und Aufmerksamkeitsstörungen.

Vesselness for Text Detection in Historical Document Images - Hofmann, Simon; Gropp, Martin; Bernecker, David; Pollin, Christopher; Maier, Andreas; Christlein, Vincent (2016 IEEE International Conference on Image Processing (ICIP), 2016)
UnivIS-Import:2017-12-18:Pub.2016.tech.IMMD.IMMD5.vessel
Keywords: Historical document analysis; RootSIFT; Text detection; Vesselness; VLAD